Bullying and school disruption assessment: studies with Portuguese adolescent students - Veiga, Feliciano Henriques (2012)
Problem Statement: The question of bullying and school disruptive behavior has emerged as a powerful issue in Portuguese educational context. The lack of evaluation instruments, with studied psychometric characteristics, has constituted a problem. Purpose of Study: School disruption and bullying assessment, in Portuguese adolescents, was the focus of this research. Research Methods: The psychometric qualities — internal consistency and the external validity — were analyzed in different scales. Findings: The analyses carried out confirm the scales as reliable and valid instruments. Conclusions: These instruments may be a useful avenue for teachers, psychologists and other education professionals.